Timeliness of Point-of-Care Viral Load Results Improves Human Immunodeficiency Virus Monitoring in Nigeria. (24th July 2022) - Chaplin, Beth; Agbaji, Oche; Reyes Nieva, Harry; Olatunde, Bola; Chang, Charlotte; Mitruka, Kiren; Sule, Halima; Dajel, Titus; Zee, Aaron; Ahmed, Mukhtar L; Ahmed, Isah; Okonkwo, Prosper; et al.
Abstract: Background: Human immunodeficiency virus (HIV) viral load (VL) monitoring is critical for antiretroviral therapy (ART) management. Point-of-care (POC) VL testing has been reported to be feasible and preferred over standard-of-care (SOC) testing in many low- and middle-income country settings where rapid results could improve patient outcomes. Methods: The timeliness of receipt of VL results was evaluated in an open-label, randomized, controlled trial among patients newly initiating ART. Clinical outcomes with POC VL monitoring using Cepheid Xpert vs SOC VL at Jos University Teaching Hospital and Comprehensive Health Centre Zamko in Nigeria were assessed. We determined time between specimen collection and recording of VL in patient charts, receipt of results, and ART switch for those who met virologic failure criteria. Results: Between April 2018 and October 2019, we screened 696 ART-naive individuals; 273 were randomized to POC and 268 to SOC HIV-1 VL testing. Participants in the POC arm received VL results significantly faster than those in the SOC arm (0.1 median days, interquartile range [IQR], 0.1–0.2 vs 143.1 days, IQR, 56.0–177.1, respectively; P < .0001). Participants in the POC arm with confirmed virologic failure vs those in the SOC arm were switched more rapidly to a second-line regimen (0 median days, IQR, 0–28 vs 66 days, IQR, 63–123, respectively; P = .03). Conclusions: POC VL testing resulted in significant improvement in the timeliness of VL result receipt by patients and use for effective HIV clinical management. In patients experiencing VL failure, POC monitoring enabled prompt switching to second-line ART regimens. Clinical Trials Registration: NCT03533868. Abstract : In a randomized, controlled trial in Nigeria, patients randomized to point-of-care human immunodeficiency virus type 1 viral load testing received their test results significantly faster than those receiving standard-of-care laboratory-based testing. Patients with confirmed virologic failure were switched more rapidly to a second-line regimen.